Optimization of Industrial Development Based on Local Potential in Tanjungpinang - Nurhasanah; Ezky Tiyasiningsih (Kusuma Negara Business School, 2023)
Industrial development based on local resources is part of local economic development. This is not something new, but the concept of local economic development and its implementation techniques continue to evolve. In general, regional or local economic development is essentially an effort to strengthen local economic competitiveness for regional economic development and the accumulation of these activities will have a major impact on the development of national economic competitiveness and strengthening national economic competitiveness. Local Economic Development itself is essentially